IMPLEMENTASI EDUCATION FOR SUSTAINABLE DEVELOPMENT GOALs (ESDG) MELALUI DESAIN INSTRUKSIONAL BERMUATAN SUSTAINABILITY MENGGUNAKAN APLIKASI WORDWALL - HARYANTI, ENY; Ervina Eka Subekti; Rizky Esti Utami; Anita Chandra Dewi; Arisul Ulumuddin; Fajar Ari Widiyatmoko (Ininnawa : Jurnal Pengabdian Masyarakat, 2024)
It is known that every nation in the world, including Indonesia and Thailand, must be able to realize the 17 goals in the Sustainable Development Goals (SDGs). Achieving the SDGs can bring prosperity to humans in the current and future generations. Education is an important strategy in achieving the SDGs. This is the importance of Education for Sustainable Development (ESD) for teachers to understand. Teachers, as the spearhead in education, must be able to realize in learning the instilling of a sustainability mindset in students with interesting learning, in accordance with the needs of students as a generation living in the 21st century, which is the digital era. This Community Service Program is implemented through the pre-implementation stage, implementation stage and program evaluation and sustainability stage. The results of PkM activities are that participants understand about ESD, and can create instructional designs for learning with sustainability content using the Wordwall application. These results provide teachers with the skills to carry out innovative learning with a nurturant effect, namely students have a sustainability mindset. Keywords: Instructional Design, Sustainability, Wordwall